2010
DOI: 10.1590/s0004-282x2010000100008
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders frequency in post-polio syndrome patients caused by periodic limb movements

Abstract: Post-polio syndrome (PPS) in individuals with polio longer than 15 years is characterized by weakness and/or muscle fatigue, deficit of deglutition and breath and periodic limb movements (PLM) during sleep. We undertook a review of 99 patients with PPS, and assessed the frequency of PLM through polysomnographic recordings at our sleep disorders unit. The total number of PLM, total time of sleep (TTS), efficiency of sleep (EfS), awaking index (AI) and apnea-hypopnea index (AHI) were analyzed. Sixteen patients p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In the literature on the PM epidemics, however, other symptoms are described during the acute phase: pain, spasms, hypersensibility, and excitability [19,36]. Our study showed that IwHP also late in life experience a variety of symptoms that cannot be attributed to lesions of the anterior horn.…”
Section: Discussionmentioning
confidence: 52%
“…In the literature on the PM epidemics, however, other symptoms are described during the acute phase: pain, spasms, hypersensibility, and excitability [19,36]. Our study showed that IwHP also late in life experience a variety of symptoms that cannot be attributed to lesions of the anterior horn.…”
Section: Discussionmentioning
confidence: 52%
“…Numerous studies reported the increased frequency of RLS and periodic limb movement of sleep (PLMS) in neurological diseases often associated with fatigue ; however, a limited interest has been devoted to its possible occurrence in PPS. Although sleep disorders, including RLS and PLMS, have been described in PPS patients , there are no previous case−control studies regarding the prevalence of RLS in the PPS population. In fact comorbidity of PSS and RLS was first described in a single patient case report .…”
Section: Discussionmentioning
confidence: 99%
“…Viana et al found a circadian trend of fatigue in PPS, but they did not evaluate RLS symptoms or potential association of PLMS with disturbed sleep although they showed pathological PLMS in more than one third of PPS as reported elsewhere (4). Therefore, we conjecture that a circadian variation of fatigue may be related to unrecognized RLS symptoms in PPS previously reported in few PPS cases (3, 5).…”
mentioning
confidence: 89%